Influence of admission blood glucose and hemoglobin A1c on outcome of acute myocardial infarction - Hanan E. Zaghla; Mahmoud A. Elbadry; Alaa M. Ashour; Mohamed M. Abdelfatah (SpringerOpen, 2014)
Introduction Patients either with or without a prior history of diabetes mellitus may present with hyperglycemia during acute myocardial infarction (AMI); it is uncertain whether hyperglycemia upon admission, irrespective of the diagnosis of diabetes, remains an independent predictor of in-hospital morbidity and mortality. Aim of the study We aimed in this study to assess the impact of admission blood glucose level on the hospital course and outcome in patients presenting with AMI in ICU. Patients and methods We included 50 patients with AMI divided into two groups: group I included 30 patients with admission blood glucose level less than 180 mg/dl and group II included 20 patients with admission blood glucose level 180 mg/dl or more. Group I was subdivided into group IA including 16 patients with HbA1c less than 6% and group IB including 14 patients with HbA1c of 6% or more. All patients were subjected to complete history taking and complete clinical examination; 12-lead ECG was performed for every patient and routine laboratory investigations including cardiac enzymes, admission blood glucose level, and HbA1c were estimated at the time of admission of the patients. Results There was significant correlation between admission blood glucose level and history of diabetes mellitus and history of smoking (P = 0.000 and 0.008, respectively). There was also significant correlation between admission blood glucose level and complications of myocardial infarction including sinus tachycardia, arrhythmia, and ICU length of stay (P = 0.008, 0.002, and 0.000, respectively). However, HbA1c level was not found to be correlated with any of the previous parameters. Conclusion We concluded that elevated admission glucose level is a strong predictor of short-term adverse outcome in patients with AMIs. However, the prognostic value of diabetic control (i.e. hemoglobin A1c levels) in patients with AMI is still undefined.